The online teaching survival guide : simple and practical pedagogical tips - Boettcher, Judith V.; Conrad, Rita-Marie (Tantor Audio, 2019)
Covering all aspects of online teaching, this book reviews the latest research in cognitive processing and related learning outcomes while retaining a focus on the practical. A simple framework of instructional strategies mapped across a four-phase timeline provides a concrete starting point for both new online teachers and experienced teachers designing or revamping an online course. Essential technologies are explored in their basic and expanded forms, and traditional pedagogy serves as the foundation for tips and practices customized for online learning. The theory and techniques of successful online teaching can be significantly different from those used face-to-face. With more and more classes being offered online, this book provides a valuable resource for taking your course to the next level. Understand the technology used in online teaching ; Learn specialized pedagogical tips and practices ; Examine new research on cognition and learning ; Adopt a clear framework of instructional strategies. The Online Teaching Survival Guide provides that essential resource, with a customizable framework and deeper exploration of effective online teaching.